2009
DOI: 10.1111/j.1365-313x.2009.03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Unequally redundant RCD1 and SRO1 mediate stress and developmental responses and interact with transcription factors

Abstract: RADICAL-INDUCED CELL DEATH1 (RCD1) is an important regulator of stress and hormonal and developmental responses in Arabidopsis thaliana. Together with its closest homolog, SIMILAR TO RCD-ONE1 (SRO1), it is the only Arabidopsis protein containing the WWE domain, which is known to mediate protein-protein interactions in other organisms. Additionally, these two proteins contain the core catalytic region of poly-ADP-ribose transferases and a conserved C-terminal domain. Tissue and subcellular localization data ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
362
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(367 citation statements)
references
References 42 publications
5
362
0
Order By: Relevance
“…The locus CC2448 was functionally assigned to Poly-ADP-ribose transferase. Radical-induced cell death1 (RCD1) and proteins similar to RCD1, which contained the core catalytic domain of poly-ADPribose transferase, were important regulators of stress and developmental responses in plants (Jaspers et al, 2009). Our results suggested that this locus might be involved in climatic adaptation of C. Fargesii, especially associated with climatic extremes such as precipitation of driest and coldest quarter.…”
Section: Figurementioning
confidence: 88%
“…The locus CC2448 was functionally assigned to Poly-ADP-ribose transferase. Radical-induced cell death1 (RCD1) and proteins similar to RCD1, which contained the core catalytic domain of poly-ADPribose transferase, were important regulators of stress and developmental responses in plants (Jaspers et al, 2009). Our results suggested that this locus might be involved in climatic adaptation of C. Fargesii, especially associated with climatic extremes such as precipitation of driest and coldest quarter.…”
Section: Figurementioning
confidence: 88%
“…While RUP1/RUP2 negatively regulate UV-B signaling by interacting with UVR8 [24], the BBX24 protein fine-tunes the UV-B responses by impinging on HY5. The BBX24-interacting protein RCD1 [19] , supplemented with white light. UV-B radiation from the lamps was filtered through cellulose acetate film to block potential UV-C (+UV-B).…”
Section: Plant Growth Light and Uv-b Treatmentsmentioning
confidence: 99%
“…The expression of COP1-regulated UV-B responsive genes was enhanced in rcd1-1 mutant under UV-B radiation, indicating that RCD1 negatively regulates UV-B response [18]. Interestingly, RCD1 interacts with STO/BBX24 in vitro [19]. These findings prompted us to test whether STO/BBX24 functions in UV-B photomorphogenic responses.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Nagaoka and Takano (2003) showed that Arabidopsis plants overexpressing BBX24 had an enhanced tolerance to salty media. 55 BBX24 interacts in yeast-two-hybrid assays with the hormone and abiotic stress regulator CLONE EIGHTY-ONE/ RADICAL INDUCED CELL DEATH1 (CEO/RCD1) 56,57 and with COP1, a negative regulator of photomorphogenesis. 58 Holm and colleagues (2001) described a conserved amino-acid motif shared by BBX24, BBX25 and HY5 (V-P-E/D-Φ-G; Φ = hydrophobic residue) which is needed for a correct interaction with the WD40 domain of COP1.…”
Section: Introductionmentioning
confidence: 99%